Positive impact of oral hydroxychloroquine and povidone-iodine throat spray for COVID-19 prophylaxis: An open-label randomized trial. (May 2021) - Seet, Raymond Chee Seong; Quek, Amy May Lin; Ooi, Delicia Shu Qin; Sengupta, Sharmila; Lakshminarasappa, Satish Ramapatna; Koo, Chieh Yang; So, Jimmy Bok Yan; Goh, Boon Cher; Loh, Kwok Seng; Fisher, Dale; Teoh, Hock Luen; Sun, Jie; et al.
Highlights: We studied chemoprophylaxis of agents that could reduce spread of SARS-CoV-2 infection. Oral hydroxychloroquine and povidone-iodine throat spray reduced SARS-CoV-2 infection. Oral hydroxychloroquine and povidone-iodine throat spray use were well-tolerated. Infection rates did not significantly differ with oral ivermectin and zinc/vitamin C. Two repurposed agents reduced spread of COVID-19 in high transmission settings. Abstract: Background: We examined whether existing licensed pharmacotherapies could reduce the spread of coronavirus disease 2019 (COVID-19). Methods: An open-label parallel randomized controlled trial was performed among healthy migrant workers quarantined in a large multi-storey dormitory in Singapore. Forty clusters (each defined as individual floors of the dormitory) were randomly assigned to receive a 42-day prophylaxis regimen of either oral hydroxychloroquine (400 mg once, followed by 200 mg/day), oral ivermectin (12 mg once), povidone-iodine throat spray (3 times/day, 270 μg/day), oral zinc (80 mg/day)/vitamin C (500 mg/day) combination, or oral vitamin C, 500 mg/day. The primary outcome was laboratory evidence of SARS-CoV-2 infection as shown by either: (1) a positive serologic test for SARS-CoV-2 antibody on day 42, or (2) a positive PCR test for SARS-CoV-2 at any time between baseline and day 42. Results: A total of 3037 asymptomatic participants (mean age, 33.0 years; all men) who were seronegative to SARS-CoV-2 at baseline were included in the primary analysis. Follow-up was nearly complete (99.6%). Compared with vitamin C, significant absolute risk reductions (%, 98.75% confidence interval) were observed for oral hydroxychloroquine (21%, 2–42%) and povidone-iodine throat spray (24%, 7–39%). No statistically significant differences were observed with oral zinc/vitamin C combination (23%, –5 to +41%) and ivermectin (5%, –10 to +22%). Interruptions due to side effects were highest among participants who received zinc/vitamin C combination (6.9%), followed by vitamin C (4.7%), povidone-iodine (2.0%), and hydroxychloroquine (0.7%). Conclusions: Chemoprophylaxis with either oral hydroxychloroquine or povidone-iodine throat spray was superior to oral vitamin C in reducing SARS-CoV-2 infection in young and healthy men.